APPLICATION OF ISLAMIC ECONOMIC LAW OF MURABAHAH FUNDING IN ISLAMIC BANKING - Nunung Rodliyah (UBL, 2016)
The Bank is a financial institution that has a strategic role in developing national development. Banking world recognize two systems, namely the economic system of conventional and Islamic economic system. Conventional economic systems are commercial banks and rural banks. Islamic bank is a bank that uses the basic Islamic law and doing business with the Islamic principles referring to the Al - Quran and Al -Hadith and Al- Ro'yu (reasonable minds). One Islamic products that exist in Islamic banking is murabaha financing. Their financing channeled Islamic bank will always involve risks, namely the risk of losses due to non-current provision of financing or financing problems. The problem in this research is how the application of the principle of economic law on the Sharia to financing murabaha Islamic Banking and rescue efforts against murabaha financing is problematic. This study is a normative legal research with descriptive type. This research is using the normative legal - normative approach applied to the type of normative approach, analytical legal substance (approach of legal content analysis). The data used are secondary data consists of primary legal materials, secondary law and tertiary legal materials. The findings of the research that murabahah on Islamic Banking uses wakalah that empowers the customer to buy the object or objects that have been agreed in the contract , so that execution of the contract murabaha does not conflict with existing provisions , whether the provisions issued by the National Sharia Council of Indonesian Ulema Council No. 04/DSN - MUI / IV / 2000 on murabaha and Bank Indonesia Regulation Number 7/46 / PBI / 2005 on Contract Assembler and Disbursement For banks Conducting Business Based on the principle of murabaha financing Syariah. Upaya rescue troubled on researching Islamic Banking customers , when acting in good faith efforts to rescue the troubled murabaha financing is done through financing by way of rescheduling restructuring (rescheduling), reconditioning (back requirements) , and restructuring (restructuring).